Racing Clean in a Tainted World: A Qualitative Exploration of the Experiences and Views of Clean British Elite Distance Runners on Doping and Anti-Doping - Shelley, Jake; Thrower, Sam N.; Petróczi, Andrea (Frontiers in Psychology, 2021)
Background: Doping has been a prominent issue for the sport of athletics in recent years. The endurance disciplines, which currently account for 56% of the global anti-doping rule violations in athletics, appear to be particularly high risk for doping. Objective: Using this high-risk, high-pressure context, the main purpose of this study was to investigate the human impact of doping and anti-doping on “clean” athletes. The secondary aim of the study was to better understand the reasons for, and barriers to, competing “clean” among this group of athletes. Method: Semi-structured interviews were conducted with 11 elite distance runners from the UK to explore: (1) the reasons and motivations for competing clean. (2) Perceptions of the anti-doping system, and experiences of being part of that system. (3) Views on the prevalence and causes of doping and the impact of doping on the lives of clean athletes. The interviews were audio-recorded, transcribed verbatim, and analysed using Reflexive Thematic Analysis. Results: Four major themes were identified: (1) The participants in this study have not been tempted to use prohibited substances or methods; they compete in their sport for the personal satisfaction of seeing how good they can be, rather than in pursuit of winning at all costs. (2) Anti-doping does not currently prevent doping effectively and is not implemented evenly across the globe. (3) Doping was perceived as a major issue and was felt to be borne out of certain sporting cultures in which doping is enabled. (4) Doping has impacted the careers of clean athletes in irreversible ways and presents a continuing challenge to the psychological preparation for competition. Conclusions: Clean athletes suffer negative consequences from both doping and anti-doping. ADOs must collaborate across borders to ensure a more even implementation of anti-doping activities, to facilitate a more level playing field on the global stage. ADOs must also acknowledge the existence of a large group of athletes who would never consider deliberately doping and make anti-doping work for these athletes too.